2017
DOI: 10.1007/s10811-017-1204-5
|View full text |Cite
|
Sign up to set email alerts
|

Crude fucoidan content in two North Atlantic kelp species, Saccharina latissima and Laminaria digitata—seasonal variation and impact of environmental factors

Abstract: Fucoidans are sulphated fucose-rich polysaccharides predominantly found in the cell walls of brown algae. The bioactive properties of fucoidans attract increasing interest from the medico-pharmaceutical industries and may drive an increase in demand of brown algae biomass. In nature, the biochemical composition of brown algae displays a seasonal fluctuation driven by environmental factors and endogenous rhythms. To cultivate and harvest kelps with high yields of fucoidans, knowledge is needed on seasonal varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 51 publications
1
34
2
1
Order By: Relevance
“…Extraction procedures can affect the molecular weight of fucoidans and molecular weight is an important factor that can influence fucoidan bioactivity [ 6 ]. The enzyme-assisted extraction procedure was expected to result in intact fucoidans with larger molecular weight than that obtained by chemical extraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction procedures can affect the molecular weight of fucoidans and molecular weight is an important factor that can influence fucoidan bioactivity [ 6 ]. The enzyme-assisted extraction procedure was expected to result in intact fucoidans with larger molecular weight than that obtained by chemical extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Polysaccharides are intensively studied due to their useful bioactivities, such as antioxidant [ 1 ], antitumor [ 2 ], neuroprotective [ 3 ], anti-inflammatory, and anticoagulant [ 4 ]. Fucoidan content and monosaccharide composition depend on many factors, such as seaweed species, environmental conditions, collecting time, and methods used for polysaccharide extraction and purification [ 5 , 6 , 7 ]. Fucoidans are heteropolymers that are primarily composed of fucose, but may include other sugars, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Seaweed tends to accommodate the high wave and water current velocity with the tough cell wall structure. Study of Bruhn et al 29 showed that mechanical stress in the form of increased exposure high wave and high wind speed could increase FCSPs content in brown seaweed Saccharina latissima and Laminaria digitata growing around Aarhus water area Denmark , although this linear relationship between FCSPs and exposure could not be generalized to all environmental condition. Besides its function in forming cell wall integrity, FCSPs is known to play an important role in regulating the cell osmotic pressure under extreme salinity conditions 28,30 .…”
Section: Proximate and Water-soluble Componentsmentioning
confidence: 98%
“…Besides its function in forming cell wall integrity, FCSPs is known to play an important role in regulating the cell osmotic pressure under extreme salinity conditions 28,30 . Other factors such as reproduction, season, part of the thallus, and age of plant will determine FCSPs content in algae tissue 29,31,32 . The resulted FCSPs were analyzed for its sugar profile using HPLC-RI.…”
Section: Proximate and Water-soluble Componentsmentioning
confidence: 99%
“…2018), and other environmental factors (Ehrig and Alban 2015, Bruhn et al. 2017). Thus, the variation of growth traits and dynamic changes in the content of carbohydrate components may help us to understand the biological process of carbohydrate metabolism.…”
mentioning
confidence: 99%